A visual analog scale to measure psychological and physical pain: A preliminary validation of the PPP-VAS in two independent samples of depressed patients - Jollant, Fabrice; Voegeli, Géraldine; Kordsmeier, Nolan C.; Carbajal, Jessica M.; Richard-Devantoy, Stéphane; Turecki, Gustavo; Cáceda, Ricardo (Progress in neuro-psychopharmacology & biological psychiatry, 2019)
Psychological pain lies at the heart of human experience. However, it may also be abnormally intense and/or prolonged in pathological states, with negative outcomes. A simple and reliable measure of psychological pain for clinical use would be useful. In this study, we present a preliminary validation of a simple visual analog scale jointly measuring psychological and physical pain. Two samples of adult (non elderly) depressed patients and healthy controls were independently recruited in two locations in Canada and the USA (N = 46/48 and 200/20, respectively). Six dimensions were successively scored on a paper visual analog scale measuring current, mean and worst pain over the last 15 days, for physical then psychological pain. All physical and psychological pain dimensions discriminated depressed from non-depressed subjects. Among depressed patients, psychological pain scores were higher than physical pain scores for a given period of assessment. Moreover, correlations between dimensions from the same pain category (physical or psychological) were higher than between different pain categories. Psychological pain was mainly correlated with depression and hopelessness scales while physical pain was mainly correlated with anxiety scales. Secondary analyses showed that psychological (and some physical) pain measures were correlated with suicidal ideas in one location, but no difference in pain scores was found between patients with vs. without a history of suicidal acts in both samples. Childhood trauma positively correlated with several pain dimensions. The PPP-VAS appears to be a valid tool in terms of discriminative capacities and convergent-divergent validities. Validation in different samples, including adolescents and elderly, and in various psychiatric and medical conditions will have to be conducted, in addition to the assessment of concurrent and predictive validities, and the confirmation of sensitivity to change. The role of psychological pain in the suicidal process needs to be further elucidated. •The PPP-VAS is a simple analog scale for physical and psychological pain.•An initial validation was conducted in depressed patients and healthy controls.•The PPP-VAS showed good discriminative and convergent/divergent validities.•The association with suicidality was not as strong as expected.